Evaluation of knowledge and perception of newborn jaundice among parturient mothers in a secondary health care centre in the Niger Delta region of Nigeria (Bangladesh Journal of Medical Science, 2014)
Background: Newborn jaundice has remained one of the leading causes of neonatal morbidity and mortality in sub-Saharan Africa. It is believed that delays in detection and/or inappropriate treatment may largely be responsible for this. Given that most mothers are now discharged home 24 hours after a normal delivery, the responsibility to detect jaundice in the new-born and take appropriate decision now rest with the mothers. This study therefore sought to evaluate the knowledge and perception of newborn jaundice among parturient mothers. Method: This study was a descriptive cross-sectional study carried out among 255 parturient mothers at the lying-in ward of Mariere Memorial Central Hospital. A structured, pre-tested, interviewer administered questionnaire was used to obtain information from the mothers. SPSS version 16 was employed in the analysis of the data. Results: Of the 255 parturient mothers interviewed, only 156 (61.2%) affirmed their awareness of newborn jaundice and only these mothers were further analysed. Their mean age was 30.2±5.4 and a median parity of 2. Thirty-seven (23.7%) of the mothers had tertiary education and just about half (50.6%) of the mothers knew that newborn jaundice presents with yellowish discoloration of the body and sclera. Three (1.9%) of the mothers knew that haemolysis is an underlying cause of jaundice and four (2.6%) mothers each correctly mentioned phototherapy and exchange blood transfusion as treatment modalities. Health talk given at the antenatal clinic was the source of information by 81 (51.9%) of the mothers. Conclusion: This study showed that the knowledge of risk factors/causes, treatment and complication of newborn jaundice by mothers is unsatisfactory. DOI: http://dx.doi.org/10.3329/bjms.v13i3.16521 Bangladesh Journal of Medical Science Vol.13(3) 2014 p.292-297